Therapeutic Options for the Treatment of Pulmonary Hypertension - Tamanna, Rownak Jahan (University Heart Journal, 2011)
The therapy of pulmonary hypertension depends on the identification of underlying contributing factors. pulmonary arterial hypertension (PAH), which can be idiopathic or related to connective tissue disease, portal hypertension, HIV disease, ingestion of certain drugs or toxins, or congenital heart disease, had no specific therapy until recently. However, the past decade has seen remarkable progress, and these heretofore devastating and usually lethal forms of pulmonary hypertension now often respond to one form of therapy or another, leading to improved functional capacity and even survival. The following will consider the major pharmacotherapy’s now available for PAH and suggest a framework for therapeutic decision-making. Key word: Pulmonary hypertension DOI: 10.3329/uhj.v6i1.7193 University Heart Journal Vol.6(1) 2010 pp.37-40